Perancangan Website Desa Karanggeneng serta Mengoptimalkan Limbah Plastik Guna Budidaya Hidroponik - Puspitasari, Norma; Pamungkas, Canggih Ajika; Fernando, Widar (Politeknik Indonusa Surakarta, 2023)
The effect of hydroponics using used goods in growing vegetables greatly influences the surrounding environment so that it is effective and efficient so that it can reduce plastic waste in the environment. In Karangjati Village, Karanggeneng, there is a Village Park which is a project of the Boyolali city government. This project is intended for the residents of Boyolali in each village to create a village garden planted with vegetables in order to improve children's nutrition in each village in the Boyolali area. In this activity, the village residents use the garden to plant all vegetables and when they are harvested they will be harvested and distributed to all residents. However, in its management, residents only use planting techniques using soil. In Karangjati Village, they are also not yet familiar with technology that could easily introduce the village and the park in the village. And in the end the village implemented it.